Hedging with Trees: Tail-Hedge Discounting of Long-Term Forestry Returns - Lars Hultkrantz; Panagiotis Mantalos (Örebro University School of Business, 2016)
Tail-hedge discounting is based on decomposition of returns from long-term investments in a fraction (gamma) that is correlated with consumption and another that is not. The first part is discounted at a discount rate that includes a risk premium, the other with the risk-free rate. We estimate gamma for forestry on Swedish data for stumpage prices and GDP per capita 1909- 2012. We demonstrate in three forestry cases that the result considerably changes the expected present value of long-term forestry investments.
Keywords: D61; D63; D81; D92; Q23; 330; discounting; far distant future; declining discount rates; forestry; forest economics; cost-benefit analysis